Phone and Video-Based Modalities of Central Blinded Adjudication of Modified Rankin Scores in an Endovascular Stroke Trial. Issue 12 (December 2015) - López-Cancio, Elena; Salvat, Mercè; Cerdà, Neus; Jiménez, Marta; Codas, Javier; Llull, Laura; Boned, Sandra; Cano, Luis M.; Lara, Blanca; Molina, Carlos; Cobo, Erik; Dávalos, Antoni; et al.
Abstract : Background and Purpose—: The standard outcome measure in stroke research is modified Rankin scale (mRS) evaluated by local blinded investigators. We aimed to assess feasibility and reliability of 2 central adjudication methods of mRS in the setting of a randomized endovascular stroke trial. Methods—: This is a secondary analysis derived from the Randomized Trial of Revascularization With Solitaire FR Device Versus Best Medical Therapy in the Treatment of Acute Stroke Due to Anterior Circulation Large Vessel Occlusion Presenting Within Eight Hours of Symptom Onset (REVASCAT) trial cohort. Primary outcome was distribution of mRS at 90 days. Local evaluation was done by certified investigators masked to treatment assignment using structured face-to-face interviews. In addition, central assessment was performed by 2 independent raters via structured phone interview (n=120) and via video recordings of the face-to-face interviews with local investigators (n=106). Interrater agreement was evaluated using kappa and discordance statistics. Sensitivity analyses for the primary end point using different adjudication approaches were performed. Correlation between mRS obtained with each modality and 24-hour follow-up infarct volumes was studied. Results—: Using local evaluation as the reference, higher agreement rates were noted with central video than with central phone evaluations ( k w 0.92 [0.88–0.96] versus 0.77 [0.72–0.83]). Discrepancies in mRS scoring between local and central raters (phone- and video-based) were similar in both treatment allocation arms. Sensitivity analyses showed benefit of endovascular treatment irrespective of adjudication method, but higher odds ratios were observed with local evaluations. Final infarct volume was similarly correlated with mRS across all 3 evaluation modalities. Conclusions—: Central adjudication of mRS is feasible, reducing interrater variability and avoiding potential problems related to lack of blinding. Our findings may have implications in the planning of future randomized acute stroke trials, especially in those including nonpharmacological interventions. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01692379.